Germination and growth of Fimbristylis miliacea biotypes resistant and susceptible to acetolactate synthase-inhibiting herbicides - C.E. Schaedler; J.A. Noldin; D. Agostinetto; T. Dal Magro; L.C. Fontana (Planta Daninha, 2013)
Weed biotypes resistant and susceptible to herbicides may have differences in their adaptive values. The aims of this study were to compare, under controlled and non-competitive condition, the growth analysis, germination features and seed weight of Fimbristylis miliacea (FIMMI) biotypes resistant and susceptible to acetolactate synthase (ALS) inhibiting herbicides. Experiments were conducted in a greenhouse and in a laboratory from October 2008 to February 2010. Two resistant biotypes (FIMMI 10 and FIMMI 12) and one susceptible biotype (FIMMI 13) were used for the studies. For the study on growth analysis, the treatments were arranged in a completely randomized experimental design with four replications and sampled at 21, 28, 35, 42, 49, 56, 69 days after emergence (DAE) and at flowering stage. For the studies on germination speed, germination and seed weight, the indexes for germination speed, percentage of germination at different temperatures and seed weight of the biotypes were determined. The results showed that the resistant biotype FIMMI 12 shows differences in all variables compared to the resistant biotype FIMMI 10 and compared to the susceptible biotype FIMMI 13, only for the evaluation at flowering. The susceptible biotype FIMMI 13 showed a higher germination speed index and higher germination rate when compared with the resistant biotypes. On the other hand, the resistant biotypes FIMMI 10 and FIMMI 12 showed higher seed weight.